MENINGKATKAN PERAN PENGURUS KMK ST.THOMAS AQUINAS SEBAGAI BENTUK PASTORAL ORANG MUDA BAGI PARA ANGGOTANYA DI FKM UNDANA - Mali, Emanuel I.D.Je’e; Rusae, Yohanes (STIPAS Keuskupan Agung Kupang, 2020)
Young people with a passionate spirit always want to move forward. They want new things. In this context, young people aspire to their true identity. In this process they also experience many confusing things, because they lack adequate guidance and assistance, especially in living the Christian faith. Many young people also feel a kind of crisis of faith, as they tend to look for something interesting and satisfying, especially in the era of advances in information and communication technology. Young people need assistance in order to form an integral identity and character. The Church pays close attention to the character building and faith formation of young people. The Church provides special guidance in dealing with Catholic youth through youth pastoral care. Fostering Christian youth is the Church's service in proclaiming the Kingdom of God. Young people are the subject of the Church's formation to produce Christian believers who are able to live gospel values. Because with gospel values, young people are able to participate and be responsible for the development of the Kingdom of God in the world. In addition, the moral attitudes of young people can be well patterned based on faith in Christ. Thus, youth pastoral is an urgent matter that needs to be developed by the Church in every pastoral activity.